Experimental Investigations on Charge Induction and Microseismic Characteristics of the Coal and Rock under Different Loading Rates - Yuchun Liu; Ling Ding; Yangfeng Zhao; Yi Fan; Hongfei Li (Shock and Vibration)
The research on charge induction and microseismic characteristics of coal and rock under different loading rates is of great significance for rockburst prediction. In this study, the coal and sandstone samples from the No. 11 mine of Pingdingshan Coal Mine are prepared. The charge induction and microseismic synchronous comprehensive monitoring system is built. The uniaxial compression tests of coal and sandstone samples under the different loading rates are conducted. The charge induction and microseismic signal characteristics in the deformation and fracture process of the coal and rock under the different loading rates are studied. The results show that, with the increase of loading rate, the compressive strength of the coal and rock samples increases and the time from the peak stress to instability failure becomes shorter. At the same loading rate, the softening failure stage time of coal is longer than that of sandstone. With the increase of loading rate, the duration of charge-induced signal and microseismic signal is longer and the events’ number and amplitude of charge signal and microseismic signal increase in the deformation and fracture process of the coal and rock. Before the instability failure, the charge-induced signal and microseismic signal have both synchronous and asynchronous signals, and the amplitude of charge-induced and microseismic signals in each channel is different, which is related to the distance from the position of each sensor to the fracture point of the sample. During the instability failure, the charge induction and microseismic signals of each channel are generated synchronously, and the signal amplitude reaches the maximum values of 50 pC and 6 × 10−3 m/s at the same time. With the increase of specimen stress, the dominant frequency of microseismic signals first increases and then decreases, while the amplitude of dominant frequency increases synchronously. The dominant frequency amplitude of microseismic signals is the largest in instability failure. With the increase of loading rate, the spectrum amplitude of microseismic signals changes little in the compaction stage, but the spectrum amplitude increases in other stages. At the same loading speed, the events’ number of the microseismic signal of coal samples after peak stress is more than that of sandstone samples, and the signal amplitude is also larger. However, the spectrum distribution range of microseismic signals of coal samples is wider than that of sandstone samples, and the spectrum amplitude of coal samples is lower than that of sandstone. With the increase of loading rate, the time of the first generation of high-amplitude signals is advanced, and the stress of specimen becomes smaller when the first generation of high-amplitude signals occurs. With the increase of loading rate, the duration of microseismic and charge signal is longer, and the mean square amplitude of charge signal is larger.